Intravitreal injection of vancomycin leading to cilioretinal artery occlusion: A case report and literature review - Chen Zhao; Miao Hao; Han Zhang; Weiyan Zhou (Journal of International Medical Research)
Cilioretinal artery occlusion is a serious condition that results in a sudden and severe decline in vision. There are various treatment methods for retinal artery occlusion, but their effect remains unclear. Cilioretinal artery occlusion post-intravitreal drug injection is rare, with no relevant reports published to date. A man in his early 50s was admitted to our department due to a nail injury to the right eye. The patient underwent exploratory and suture surgery for eyeball penetrating injury, intraocular foreign body removal, and intravitreal vancomycin injection. The patient’s preoperative visual acuity in the right eye was 0.1, which decreased to FC/5 cm one day after surgery. Wide-angle fundus photography revealed cilioretinal artery occlusion. We highly suspected that the sudden increase in intraocular pressure after intravitreal injection of vancomycin was the cause of cilioretinal artery occlusion in this case. Mouse nerve growth factor (30 μg) and anisodine hydrobromide tablets (3 mg) were used for neurotrophic and microcirculation-improving treatments. Follow-up fundus fluorescein angiography at 31 seconds on postoperative day 18 showed filling of the cilioretinal artery. At 14 months post-surgery, the patient’s right eye visual acuity recovered to 0.1. In conclusion, cilioretinal artery occlusion post-intravitreal vancomycin injection is an extremely rare but severe complication that significantly affects vision. Early diagnosis and timely treatment are vital in such cases.